155k views
0 votes
PLEASE HELP! 25 PTS!!

Consider function f and g.


f(x)=(x-16)/(x^2+6x-40) for
x\\eq-10 and
x\\eq 4


g(x)=(1)/(x+10) for
x\\eq -10


which expression is equal to f(x) + g(x)?

A.
(2x-12)/(x^2+6x-40)

B.
(2x-20)/(x^2+6x-40)

C.
(x-15)/(x^2+6x-40)

D.
(x-15)/(x^2+7x-30)

PLEASE HELP! 25 PTS!! Consider function f and g. f(x)=(x-16)/(x^2+6x-40) for x\\eq-example-1
User Vladimir K
by
5.7k points

1 Answer

6 votes

Answer:

Solution given:


f(x)=(x-16)/(x^2+6x-40)


g(x)=(1)/(x+10)

now

f(x)+g(x)=
(x-16)/(x^2+6x-40)+(1)/(x+10)....(1)

now

factoring x²+6x-40

we get

x²+10x-4x-40

x(x+10)-4(x+10)

(x+10)(x-4)

now substituting in equation 1 ,we get

f(x)+g(x)=
(x-16)/((x+10)(x-4))+(1)/(x+10)

taking l.c.m

=
((x-16)+(x-4))/((x-10)(x-4))

=now

opening bracket


(x-16+x-4)/(x²-10x-4x+40)

=
(2x-20)/(x²+6x-40)

So

answer is :

B.
\bold b(2x-20)/(x^2+6x-40)

User Maxim Kasyanov
by
5.7k points